Use of high kilovoltage filtered beam radiographs for detection of bronchial situs in infants and young children. Issue 5 (November 1980) - Deanfield, J E; Leanage, R; Stroobant, J; Chrispin, A R; Taylor, J F; Macartney, F J
Abstract : Determination of atrial situs is of cardinal importance in the analysis of complex congenital heart lesions, and is best predicted from bronchial situs. Previous methods for assessing bronchial morphology, however, are unsuited to the very young patient. To assess bronchial morphology, 100 consecutive patients under 18 months of age (medium 57.5 days) with suspected congenital heart disease were studied by high kilovoltage filtered beam radiographs, before cardiac catheterisation. This low radiation dose technique clearly defined bronchial anatomy in 95 patients. The lengths of the left and right main bronchi were compared and 10 cases (10%) had a ratio less than 1.5 suggesting bronchial isomerism. Discriminant function analysis based on tracheal width and bronchial length enabled clear distinction of right from left bronchi. Four patients had bilateral right and six had bilateral left bronchi. Four of these 10 cases died and had necropsy confirmation of the radiological diagnosis. Practical prediction about cardiac anatomy, particularly the systemic and pulmonary venous return, may be made when bronchial morphology is known.